Concussion knowledge and attitude of English youth rugby players: the RUCKAS-YOUTH survey - Silver, D.; Faull-Brown, R.; McClusky, R.; Brown, N.; Patterson, S.; Stokes, K.; Kemp, S. P. T. (BMJ Open Sport & Exercise Medicine, 2025)
Objective This cross-sectional study describes the concussion knowledge and attitudes of male and female 14-18 year-old school rugby union players in England.